FILSAFAT AKHLAK DALAM ETIKA PEMIKIRAN KONTEMPORER - Herman man man (Jurnal Ilmu Pengetahuan Sosial, 2013)
Basic Islamic morality contained in the minutes of that was brought by the Prophet. Minutes of the bersumberkan Qur'an and Sunnah which is manifested by bolting and way of life of the Prophet himself. Behavior and way of life of the Prophet became a role model to follow and an example of the perfection of human life both physical and spiritual. To reach the stage of personal perfection of glory, God has a human equip with original inventory so that is, with all kinds of instincts and reasonable minds and also decorated with all kinds of science that may be a way of life for the sake of fostering civilization on this earth. Due to limited sense weaknesses and limitations in reaching aspect of nature, natural good nature mahupun supernatural reality, Allah sent down His revelation as absolute guidance for human use in fostering the life and civilization in harmony with the values of a noble character. Herein lies the role of the treatise is carried by the Prophet intended to form the basis of a noble character and absolute for the entire human purposes